Mythos : Joseph Beuys, Matthew Barney, Douglas Gordon, Cy Twombly - Schneider, Eckhard; Anfam, David; Blume, Eugen; Hartley, Keith; Joselit, David; Roeck, Bernd; Schneede, Uwe M; De Werd, Guido; Kunsthaus Bregenz (Bregenz : Kunsthaus Bregenz, 2007)
Barney, Matthew ; Beuys, Joseph ; Gordon, Douglas ; Twombly, Cy ; et al.
Volume 2 / Band 2
Kunsthaus Bregenz, Bregenz, June 2 to September 9, 2007
kunstcatalogus